Money decentralization under direct democracy procedures: The case of classical Athens - Emmanouil Marios L. Economou; Nicholas C. Kyriazis; Nikolaos A. Kyriazis (Journal of Risk and Financial Management, 2021)
By analyzing the case of Athens during the Classical period (508-323 BCE) the main thesis of this paper is that under direct democracy procedures and the related institutional setup, a monetary system without a Central Bank may function relatively well. We focus on the following issues: (i) The procedures of currency issuing in the Athenian city-state, (ii) why the Athenian drachma become the leading international currency in the Mediterranean world (iii) how and towards which targets monetary policy without a Central Bank was possible (iv) defining the targets of monetary policy and the mechanisms for its implementation (v) the role of money in the economy (vi) the issue of deficit spending (vii) the reasons of the replacement of the Athenian drachma as a leading currency by others from the Hellenistic period onwards (viii) the correlation of our findings regarding the decentralized character of monetary policy in Classical Athens to today's realities, such as the issue of cryptocurrencies. Our analysis shows that monetary policy without a Central Bank was possible, with its foremost aim being the stability of the currency (mainly, silver coins) in order to enhance trust in it and so, make it an international currency which could outcompete other currencies. Since there was no Central Bank like today, monetary policy decisions were taken by the popular assembly of citizens in combination with the market forces themselves.
Keywords: E62; F50; G20; G28; N13; N23; 330; Classical Athens; Athenian currency; monetary policy and institutions; direct democracy; money decentralization; monetary globalization